Factors influencing teachers’ attrition in public basic schools in Techiman Municipality, Ghana: An embedded mixed methods study - Kyeremeh, Joseph; Adom, Dickson; Essuman, Michael Ato; Pek, Lim Seon (CV Rezki Media, 2025)
Background: The high teacher attrition rate in public primary schools in Techiman, Ghana, has become a serious problem that directly impacts the quality of education and the achievement of national education development goals. Objectives: The study investigated factors that influence teachers' attrition in the Techiman Municipality. Methods: One hundred ninety-seven teachers were sampled for the study using convenience and simple random sampling techniques. This study utilized the embedded mixed methods design with descriptive survey and phenomenology as research methods to collect quantitative and qualitative datasets using questionnaires and interviews as data collection tools. The qualitative data were analyzed using thematic analysis, while the quantitative data were analyzed using descriptive and inferential statistics using the SPSS software. Results: It was found that teachers perceived salary as the major employer-related factor in teachers' attrition (relative importance index (RII) = 0.85). team member-related factors, such as the willingness of teachers to pursue another career outside education, were perceived as the primary factor of attrition (RII = 0.78). In contrast, an external-related factor, such as better opportunities in some other occupations, was ranked the first major contributor to teachers' attrition (RII = 0.88). The overall assessment of the factors of attrition based on the relative importance index revealed that Employer-related factors are the major contributor to teachers' attrition (RII = 0.70). Conclusions: The study recommends that the Ghana government find innovative ways of increasing teachers' salaries as a source of motivation and offer them other incentive packages to aid in retaining them in the service.